In vitro comparison of Candida albicans adhesion and colonization on three tissue conditioners - Abbas Falah-Tafti; Abbasali Jafari Nodoushan; Feridon Soltani; Zeynab Ebrahimi-Moghadam; Farzaneh Mirzaei (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: Denture stomatitis is an important disorder as a result of denture wearing in geriatric populations caused by Candida albicans colonization. Tissue conditioners are used for better adaptation of denture surface with the oral tissues to prevent denture stomatitis; however, these materials encourage adhesion and colonization of most oral microbial flora, particularly Candida species. The aim of this study was to compare C. albicans adhesion and colonization on three commonly used tissue conditioners. Materials and methods: In this in vitro study, 18 discs, measuring 5 mm in diameter and 1 mm in thickness, from the three commonly used tissue conditioners (Visco-gel, GC-Reline, and Acrosoft( were incubated in 1´105 cfu/mL Candida albicans suspension for 48 hours at 37ºC to form an experimental biofilm. Tissue conditioner discs were then rinsed with sterile physiologic serum and finally the colonized Candia cells were cultured on Sabouraud's dextrose agar plates. Isolated colonies were counted and compared between the three disc groups using ANOVA and a post hoc Tukey test. Statistical significance was defined at p ≤ 0.05.Results: Visco-gel and Acrosoft tissue conditioners with the average colonization of 14378.9 cfu/mL and 32227.2 cfu/mL had the maximum and minimum viable colonized Candida cells, respectively in the present study (p value = 0.0001(. Gc-Reline tissue conditioner exhibited moderate Candida colonization with 22342.8 cfu/mL. Conclusion: The results of the current study showed that different tissue conditioners had different resistance to in vitro adhesion and colonization of Candida albicans. Use of tissue conditioner with more inhibitory properties for Candida colonization is suggested. Key words: Bacterial adhesion, Candida albicans, Tissue conditioning.